Pengaturan Tentang Status Hukum âIllegal Immigrantâ Berdasarkan Hukum Internasional, Hukum Nasional Dan Penanganannya Di Indonesia - Aini, Desy Churul (Jurnal Selat, 2015)
Indonesia constitutes state transit to divide illegal immigrant , asylum and refuge e seeker.International protection on refugees is managed in Convention 1951 and Protocols 1967 about status of Refugee. Indonesia until now havenât ratification Convention 1951 and Protocols 1967 about status of Refugee, so no special national law that manages about status of and in the presence asylum seeker and Refugee at Indonesian. Handle on illegal immigrant , asylum and refugee seeker performed by Immigration General directorate as institute of expatriate supervisor that given by authority by Indonesia Government to do collaboration and asks for UNHCRâS help (United Nations High Commissioner for Refugees) and IOM (International Organizations for Migrant). About problem emerging while authority state establishment sentences illegal immigrant this becomes overlap among drd that institute. Keywords: Jurisdictional State, illegal immigrant